Pemanfaatan Ruang Punden Pada Tradisi Nyadranan Desa Klepek Kabupaten Kediri - Muhammad Andi Finaldi Nur Tantyo; Lisa Dwi Wulandari; Agung Murti Nugroho (RUAS, 2022)
Local wisdom of Klepek village involves a sacred space called punden. The implementation of the tradition with punden as a sacred space is an embodiment of the inner responsibility and gratitude of the community to the ancestors who built the village. Traditional activities involving punden consist of the nyadranan tradition, barikan, preparation for celebrations and thanksgiving after harvest. The focus of this research is on the nyadranan tradition. This study uses a qualitative method. Data from the object of observation was studied descriptively. The belief of the people of Klepek Village who believe punden as a sacred place results in the use of space. With the use of space for sacred activities, it can also be seen the factors that form it, namely: activity, purpose, time and actors involved. The interaction of these factors with the space used shows the meaning of space.